Pengaruh Pemberian Emras Terhadap Pertumbuhan dan Hasil Tanaman Buncis (Phaseolus vulgaris L.) pada Lahan Rawa Lebak - Zarmiyeni Zarmiyeni; Farida Adriani; Majedi Majedi (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2013)
Beans are a kind of edible beans. Beans are rich in protein and vitamins that help lower blood pressure and monitor blood sugar metabolism and are equated with being eaten by those who suffer from diabetes or hypertension. High fiber and enzyme content can help you lose weight. In peanut cultivation it needs to be optimized considering the consumption needs are not comparable with production, One way to increase the productivity of peanut plants is proper fertilization, such as by using organic fertilizers. This study aims (i) to determine the effect of EMRAS on the growth and yield of beans (Phaseolus vulgaris L.) on swampy swamp land. (ii) Getting the best concentration between EMRAS and growth and yield of beans (Phaseolus vulgaris L.) on swamp swamp land. This research was carried out on swamp swamp land in Teluk Buluh Village, Banjang District, Hulu Sungai Utara Regency in May - July 2013, using a Randomized Block Design (RBD), with 6 treatments and 4 replications, resulting in 24 experimental units and each experiment. consists of 2 sample plants, so that the total sample is 48 plants. The factors tested were the provision of EMRAS, e0 = 0% (0 l/beds), e1 = 25% (0,25 l/beds), e2 = 50% (0,5 l/beds), e3 = 75% (0,75 l/beds), e4 = 100% (1 l/beds) and e5 = 125% (1,25 l/beds). The results showed that the observation variables of EMRAS administration affected plant height, number of productive branches, number of pods per plant, and pod wet weight per plant with the best administration at 100% concentration (1 l / bed)